Body weight, eating practices and nutritional knowledge amongst university nursing students, Eastern Cape, South Africa - Violet L. van den Berg; Alice P. Okeyo; Andre Dannhauser; Mariette Nel (AOSIS, 2012)
Background: Health care workers need to be equipped to deal with the increasing obesity and obesity-related morbidity occurring in developing countries. Objectives: To assess weight status, eating practices and nutritional knowledge amongst nursing students at the University of Fort Hare, Eastern Cape. Method: A cross-sectional descriptive survey was conducted on 161 undergraduate (51 male and 110 female) students of the Department of Nursing Sciences at the University of Fort Hare. Body mass index, waist and hip circumferences and waist hip ratio were determined. Nutritional knowledge and eating practices were investigated by structured intervieweradministered questionnaires. Results: Statically, 49.7% were overweight or obese (58.2% of the females; 31.4% of the males) and 65.2% had waist circumferences putting them at risk for non-communicable diseases. Most did not meet the recommendations for intakes from the vegetable group (97.5% ate <3 servings per day), the fruit group (42.2% ate <2 servings per day), and the dairy group (92.6% ate <2 servings per day); whilst 78.3% ate ≥4 serving per day of sugar or sweets. Most consumed margarine, oil or fat (68.3%), sugar (59.0%) and bread (55.9%) daily, but few reported daily intakes of vegetables (12.4%), fruit (23.6%), fruit juice (21.2%) and milk (15.6%). Fewer than 50% knew the recommended intakes for vegetables, fruit, dairy, starchy foods and meat or meat alternatives. Conclusions: These nursing students had a high prevalence of overweight and obesity, poor eating habits and inadequate knowledge on key nutrition issues, which may impact negatively on their efficacy as future health ambassadors to the public.